Reliability centered maintenance / Azlan Mohd. Yusoff and Kamarudin Saleh - Mohd. Yusoff, Azlan; Saleh, Kamarudin (1996)
To provide error free work, factors such as training, tools, time and teamwork are absolutely essential for employees in any organizations. Training is essential to prepare the employees to do the job right the first time. Well maintained tools provide the means for the employee to excel. Time is necessary to ensure that the job is done right every time. A support team that works like a well-oiled clock is needed to make everything come together at the right instant and place. All four of these factors are required to reach the level of excellence needed to compete in today's challenging world. Infact, today's competitive battle is not being fought on the factory floor but is in the support areas. This is the reason that Reliability Centered Maintenance is so important to both high-tech and low-tech companies. To succeed in manufacturing today, one must have the right equipment and it must be superbly maintained. There are many problems with maintenance programs today. Some equipments gets too little, while some gets too much preventive maintenance. Operators are not trained to understand how the equipment works. They are trained to know how to run it but that is not enough. Maintenance people do not take time enough to truly understand why things fail. Maintenance reporting system as a whole are poor and do not provide the data required to diagnose complex problems. Recently, maintenance job has become very complex and demanding. The complex interface existing in much of the equipment requires a knowledge of the mechanics, programming and electronics that would challenge any engineers. With such a complex problem facing management, one proven approach to solving these seemingly insurmountable problems rests with a relatively new approach to maintenance called 'Reliability Centered Maintenance'.